A Novel N-Sulfonylamidine-Based Derivative Inhibits Proliferation, Migration, and Invasion in Human Colorectal Cancer Cells by Suppressing Wnt/β-Catenin Signaling Pathway - Xingming Zhao; Zhuo Han; Jiahui Ma; Shiqing Jiang; Xia Li (MDPI AG, 2021)
Wnt signaling has been implicated in the development and metastasis of colorectal cancer (CRC), as well as poorer outcomes. Thus, targeting the Wnt/β-catenin signaling pathway is expected to be a promising treatment option for the therapy of advanced metastatic CRC. A new N-sulfonylamidine derivative (26ag) has been confirmed to suppress the growth of tumor cells by inhibiting C-met, showing strong anti-cancer activity. In this paper, we test the effectiveness of 26ag in suppressing CRC cell proliferation, invasion, and migration. In this regard, 26ag decreased the mRNA and protein expressions of important hallmarks associated with epithelial to mesenchymal transition (EMT). Furthermore, we provide evidence that β-catenin-dependent signaling is involved in 26ag-induced Wnt/β-catenin pathway effects in CRC, using in vitro cell culture and computer docking models. Our study indicates that inhibition of Wnt/β-catenin by a novel compound, 26ag, demonstrates possibility for drug development in the therapy of CRC.